VIABILITY AND CAPACITY OF STORAGE OF CARQUEJA SEEDS COLLECTED IN THREE PLACES IN PARANÁ STATE - Santana, Andreia De Matos Silva; Carvalho, Ruy Inacio Neiva de (Scientia Agraria, 2006)
The current work had for objective to evaluate the influence of different types of packings and environments, and storage time of carqueja seeds over the physiologic quality of seeds. The work was carried out at UNICENP Vegetable Physiology Laboratory, being used seeds collected in Palmeira, São José dos Pinhais and Fazenda Rio Grande in Paraná State, Brazil. Seeds were conditioned in paper, plastic and glass packings, maintained in atmosphere and in the refrigerator. The physiologic quality of seeds was evaluated by germination test, with the following variables: proportion of germinated seeds, proportion of contaminated seeds and germination speed index (GSI). The experimental outlining used was one of the sub-subdivided portion in the time, being the main portion those of the storage conditions (atmosphere and refrigerator) and, the sub-portion, those of the packings (paper, plastic and glass). The evaluation times were 1, 2, 3, 4, 5 and 7 months after the starting of the experiment. The collection places had represented the three repetitions. The results allow to prove that seeds can be stored in differents packings, in temperatures from 4 up to 7 ºC (in the refrigerator), where their potential and germination speed increase in relation to those that keep stored in atmosphere. The factor time is associated with contamination and problems during the germination.